TRANSFORMASI NILAI NILAI POLITIK PADA KISAH NABI YUSUF DAN PENERAPANNYA DI ERA DEMOKRASI - Ramadan Termarwut; Ujang Mimin Muhaemin (Jurnal Syntax Fusion, 2026)
The story of Prophet Yusuf in the Qur’an contains profound lessons that extend beyond moral and spiritual dimensions into the realm of political ethics and governance. This study aims to analyze the narrative of Prophet Yusuf in Surah Yusuf, identify the political values embedded within the story, and examine how these values can be transformed and applied within contemporary democratic systems. The research employs a qualitative method using a library research approach. Primary data sources include the Qur’an and its classical and contemporary commentaries, while secondary sources consist of academic books, journal articles, and scholarly works on Islamic political thought and democracy. Data are analyzed thematically through a hermeneutic approach to explore contextual and substantive meanings of the narrative. The study applies the theory of political values in Islam and social transformation theory to understand how Qur’anic leadership principles may inform democratic practice. The findings indicate that the story of Prophet Yusuf presents a model of ethical leadership characterized by integrity, justice, strategic vision, accountability, crisis management, and public welfare orientation. These values are not merely theoretical ideals but constitute applicable normative principles that can strengthen democratic political culture. The research concludes that the political transformation reflected in the story of Prophet Yusuf provides a relevant ethical framework for modern governance.